DELIMITATIONS HEADING OF THE SPECIAL TECHNOLOGY FROM THE ACTUAL REFERENCE VIEW - P (Интеллектуальные системы в производстве, 2009)
In the article are present tendency resorts of activities of the Faculty of special technology Alexander Dubcek University of Trencin for science, expertly and education activities tendency. The resorts outgoing of orientation and heading of Slovak republic in the aliance grups and partners responsibilities, in ambit which is presumption of a development, production and pursuit the special technology. In the chapter are formulated departures of intended focus of activity of faculty with practical application of the resorts and present approach examples.